Structural Influencing Factors on ZnII/CdII Coordination Polymers Based on Tri‐pyridyl‐bis‐amide: Assembly, Structures, Fluorescent Sensing and Selective Photocatalysis. Issue 11 (6th March 2015) - Wang, Xiu‐Li; Chen, Nai‐Li; Liu, Guo‐Cheng; Lin, Hong‐Yan; Zhang, Ju‐Wen
Abstract: Fourteen new Zn II /Cd II coordination polymers tuned by semi‐rigid "V"‐like tri‐pyridyl‐bis‐amide ligands with different spacers and different dicarboxylates co‐ligands, namely, {[Zn(L1)(mip)]· H2 O} n (1 ), {[Zn2 (L1)2 (hip)2 ]· H2 O} n (2 ), {[Zn(L1)(oba)]· H2 O} n (3 ), {[Zn(L1)(chda)]· H2 O} n (4 ), {[Cd2 (L1)(mip)2 (H2 O)]· 2H2 O} n (5 ), {[Cd(L1)(hip)]· 4H2 O} n (6 ), {[Cd(L1)(oba)]· H2 O} n (7 ), {[Cd3 (L1)(chda)3 ]· 4H2 O} n (8 ), [Zn(L2)(mip)] n (1a ), {[Zn(L2)(hip)(H2 O)]· 3H2 O} n (2a ), [Zn(L2)(oba)] n (3a ), {[Cd(L2)(hip)]· 3H2 O} n (6a ), {[Cd(L2)(oba)]· H2 O} n (7a ), [Cd(L2)(chda)] n (8a ), [L1 = N, N′ ‐di(pyridin‐3‐yl)pyridine‐2, 6‐dicarboxamide, L2 = N, N′ ‐di(pyridin‐3‐yl)pyridine‐3, 5‐dicarboxamide, H2 mip = 5‐methylisophthalic acid, H2 hip = 5‐hydroxyisophthalic acid, H2 oba = 4, 4′‐oxybis(benzoic acid), H2 chda = trans ‐1, 4‐cyclohexanedicarboxylic acid] have been hydrothermally synthesized and structurally characterized. Complexes1 –4 based on the same L1 ligand and Zn II ion show various structures. Complex1 features a two‐dimensional (2D) network, which consists of a linear [Zn‐mip] n chain and [Zn‐L1] n left‐, right‐handed helixes. Complex2 is a twofold interpenetrating 2D→2D network. In complex3, Zn2 (L1)2 loops were connected by oba anions creating a 1D channel‐like structure. Complex4 is a 2D layer containing [Zn‐chda] n right‐handed helixs and Zn2 (L1)2 loops. Complexes5 –8 with Cd II ion exhibit different structures. Complex5 features a 1D belt structure based on Cd4 (COO)4 subunits. However, complex6 exhibits a 2D network constructed from [Cd‐hip] n ladder‐like chains and Cd2 (L1)2 loops. Complex7 shows a 1D double chain structure containing [Cd‐oba] n zigzag chain and [Cd‐L1] n meso ‐right‐handed helix. Complex8 exhibits a 2D network based on 2D [Cd‐chda] layer and 1D [Cd‐L1] n meso ‐helical chain. For complexes1a –8a based on L2 ligand, complex1a is a 2D layer containing [Zn‐mip] n linear chain and [Zn‐L2] n meso ‐helical chain. The structure of complex2a is very similar to that of3 . Complex3a exhibits a 2D grid network containing 1D [Zn‐oba] n and [Zn‐L2] n chains. Complex6a shows a 2D layer based on [Cd2 (hip)2 ] n double chain and [Cd‐L2] n chain. The structure of complex7a is very similar to that of7 . Complex8a is a 3, 5‐connected 3D framework with the Schläfli symbol of (4 2 .6 5 .8 3 )(4 2 .6), which is constructed from [Cd‐L2] n channel‐like chains and chda linkers. The structural diversity of the title complexes indicates that the tri‐pyridyl‐bis‐amide ligands with different spacers, the dicarboxylates and central metals play important roles in tuning the dimensionalities and structures of the target complexes. The title complexes exhibit excellent photocatalytic activity and selectivity for organic dyes degradation under UV light. In addition, fluorescent sensing behaviors of3, 6, 7 and7a toward different organic solvents have been investigated in detail. Abstract : Fourteen new Zn II /Cd II coordination polymers based on tri‐pyridyl‐bis‐amide were hydrothermally synthesized and characterized, which show photocatalytic activity and selectivity for the degradation of organic dyes. The fluorescent selectivity of these compounds makes them promising candidates as fluorescent sensor materials.